2016
DOI: 10.1155/2016/5126560
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Wnt/β-Catenin Signaling Pathway and Its Regulatory Role in Type I Collagen with TGF-β1 in Scleral Fibroblasts from an Experimentally Induced Myopia Guinea Pig Model

Abstract: Background. To investigate Wnt/β-catenin signaling pathway expression and its regulation of type I collagen by TGF-β1 in scleral fibroblasts from form-deprivation myopia (FDM) guinea pig model. Methods. Wnt isoforms were examined using genome microarrays. Scleral fibroblasts from FDM group and self-control (SC) group were cultured. Wnt isoforms, β-catenin, TGF-β1, and type I collagen expression levels were examined in the two groups with or without DKK-1 or TGF-β1 neutralizing antibody. Results. For genome mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 38 publications
1
17
1
Order By: Relevance
“…For example, the Wnt signaling pathway and JAK-STAT cascade were both identified as up-regulated genes. It has already been reported that the former and TGF-β/BMP play roles in the biomineralization of corals (Gutner-Hoch et al 2017;Zoccola et al 2009), in addition to being involved in collagen secretion in human cells (Li et al 2016). In the present results, the Wnt signaling pathway showed similar expression patterns to the collagen metabolic process, suggesting that it may be involved in coral skeletogenesis through the secretion of collagen.…”
Section: Discussionsupporting
confidence: 81%
“…For example, the Wnt signaling pathway and JAK-STAT cascade were both identified as up-regulated genes. It has already been reported that the former and TGF-β/BMP play roles in the biomineralization of corals (Gutner-Hoch et al 2017;Zoccola et al 2009), in addition to being involved in collagen secretion in human cells (Li et al 2016). In the present results, the Wnt signaling pathway showed similar expression patterns to the collagen metabolic process, suggesting that it may be involved in coral skeletogenesis through the secretion of collagen.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, we found that TM stimulation increased COL1A1 and TGF-β1 levels at 24 hours but reduced their expression at 48 hours in scleral fibroblasts. It has been well established that the levels of TGF-β and collagen were reduced during FD [10,43]. However, we found that, in vitro, chemically-induced ER stress had a time-dependent bidirectional regulation effect on collagen transcription.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, the cells can remodel the ECM [ 35 ]. In particular, the pressure used in this study is a type of compression, and the fate of cells is determined by the regulation of the Wnt/β-catenin signaling pathway after the recognition of compression through ECM components, such as collagen [ 33 , 41 ] and vimentin [ 42 ]. When it comes to genes that are significantly regulated by hypoxia and pressure, in particular, GPC4 decreased in both hypoxia and high-pressure conditions.…”
Section: Discussionmentioning
confidence: 99%